GEOPOLITICAL INTERESTS AND THE MAIN MEANS OF ITS IMPLEMENTATION IN THE POLITICS OF LEADING INTERNATIONAL ACTORS ON THE AFRICAN CONTINENT - Дорошко, М.; Пліс, А. (Київський національний університет імені Т. Шевченка, 2024)
The author made an attempt to comprehensively analyze the policies of the French Republic, the United States of America, the People's Republic of China, the Republic of India, and the Russian Federation with African countries and the reasons for the states' interest in deepening cooperation, in the place with the ways of their implementation. The main spheres of interaction between them are traced. Specific measures and projects taken by the specified states to intensify cooperation with African states were considered. Considerable attention is paid to the strategies of governments regarding the African continent.

У статті здійснено спробу комплексного аналізу політики Французької Республіки, Сполучених Штатів Америки, Китайської Народної Республіки, Республіки Індія та Російської Федерації щодо африканських країн. Проаналізовано причини зацікавленості держав у поглибленні співробітництва та шляхи їх реалізації. Простежено основні сфери взаємодії між ними. Розглянуто конкретні заходи та проєкти, вжиті зазначеними державами задля активізації співробітництва з державами Африки. Значну увагу приділено стратегіям урядів щодо країн Африканського контененту
ГЕОПОЛІТИЧНІ ІНТЕРЕСИ ТА ОСНОВНІ ЗАСОБИ ЇХ РЕАЛІЗАЦІЇ В ПОЛІТИЦІ ПРОВІДНИХ МІЖНАРОДНИХ АКТОРІВ НА АФРИКАНСЬКОМУ КОНТИНЕНТІ
Keywords: Africa; French Republic; United States of America; People's Republic of China; Republic of India; Russian Federation; Persian Gulf; geopolitics; economic projects; strategies; natural resources; competition; Africa; French Republic; United States of America; People's Republic of China; Republic of India; Russian Federation; Persian Gulf; geopolitics; economic projects; strategies; natural resources; competition; Африка; Французька Республіка; Сполучені Штати Америки; Китайська Народна Республіка; Республіка Індія; Російська Федерація; Перська затока; геополітика; економічні проєкти; стратегії; природні ресурси; конкуренція; Африка; Французька Республіка; Сполучені Штати Америки; Китайська Народна Республіка; Республіка Індія; Російська Федерація; Перська затока; геополітика; економічні проєкти; стратегії; природні ресурси; конкуренція